You Me Them - Apelu, Darcell Dorothy (Auckland University of Technology, 2013)
My project explores perceptions of the Pacific body through identification, specifically that of ‘being other’ within the social climate of New Zealand and the Pacific. I create a series of emblematic artworks that attempt to respond to and critique the relevance of the Understanding pamphlets produced by the ‘Polynesian Advisory Committee ‘of the Vocational Training Council (N.Z). In relation to an emerging duality of ‘otherness’ within New Zealand’s Pacific community, the concept of failure through misrepresentation is explored from the perspective autobiographical performances. This project—by means of moving image, performance and installation—investigates an ongoing negotiation between cultures in what I have come to understand as the ‘double agent’.
Keywords: Otherness; Emblematic; Art; Failure; Misrepresentation; Performance; Moving image; Polynesian; Pakeha